Postcaesarean open-heart surgery for Streptococcus sanguinis infective endocarditis - Kongwattanakul, Kiattisak (BMJ Publishing Group, 2013)
A 33-week pregnant (gravida 3), 29-year-old woman was transferred for management of Streptococcus sanguinis infective endocarditis. A vegetation was present on the posterior leaflet of the mitral valve with moderate mitral regurgitation. On admission (day 1), the ultrasound examination revealed splenic abscesses and retarded intrauterine growth albeit with normal vessels. The fetal heart rate was 140 bpm. On day 11, the baby was delivered by Caesarean, and then the mother underwent tubal ligation followed by a mitral valve repair. The splenic abscess was treated with antibiotics. The woman was clinically stable and recovered uneventfully. This successful outcome was achieved by a strategic (optimal and sequential) timeline for selecting the mode of delivery and type of mitral valve correction.